Moving from rhetoric to action: how Africa can use scientific evidence to halt the COVID-19 pandemic - Olushayo Oluseun Olu; Joy Luba Lomole Waya; Sylvester Maleghemi; John Rumunu; David Ameh; Joseph Francis Wamala (BMC, 2020)
Abstract The ongoing pandemic of the coronavirus disease 2019 has spread rapidly to all countries of the world. Africa is particularly predisposed to an escalation of the pandemic and its negative impact given its weak economy and health systems. In addition, inadequate access to the social determinants of health such as water and sanitation and socio-cultural attributes may constrain the implementation of critical preventive measures such as hand washing and social distancing on the continent. Given these facts, the continent needs to focus on targeted and high impact prevention and control strategies and interventions which could break the chain of transmission quickly. We conclude that the available body of scientific evidence on the coronavirus disease 2019 holds the key to the development of such strategies and interventions. Going forward, we recommend that the African research community should scale up research to provide scientific evidence for a better characterization of the epidemiology, transmission dynamics, prevention and control of the virus on the continent.